Operationalizing Nollkaemper’s and Peters’ theories on International Law within The Avoid, Align, Contest Framework for Domestic Courts - Ibrahim Hanif (Faculty of Law, Universitas Gadjah Mada, 2025)
Abstract This paper examines how domestic courts interact with international law through the lens of the “Avoid, Align, Contest” framework, applied to two leading theories: Nollkaemper’s vision of international law as a rule of law, and Peters’ conception of it as a global constitution. Nollkaemper emphasizes judicial alignment and legal coherence, requiring strong institutional capacity to enforce international norms. Peters, by contrast, allows courts greater flexibility to contest or avoid international law when grounded in shared constitutional values. By mapping each theory onto the posture model, the paper clarifies not only expected judicial behavior, but also the institutional and normative conditions required for courts to operate effectively within these theoretical frameworks. Intisari Makalah ini mengkaji bagaimana pengadilan domestik berinteraksi dengan hukum internasional melalui kerangka ‘Menghindar, Menyesuaikan, dan Menggugat’ (Avoid, Align, Contest), yang diterapkan pada dua teori utama: pandangan Nollkaemper tentang hukum internasional sebagai suatu tata hukum (rule of law), dan gagasan Peters tentang hukum internasional sebagai konstitusi global. Model “postur” ini berasal dari pengamatan empiris terhadap banyak pengadilan domestik, sementara kedua teori tersebut berbeda secara filosofis; makalah ini menerapkan kembali model postur tersebut pada tingkat teoretis. Makalah ini menunjukkan bahwa komitmen teoretis (tata hukum vs. konstitusi global) secara implisit merumuskan ekspektasi yang berbeda terhadap postur yudisial.